Antecedents and Effects of Job Satisfaction on Organizational Commitment and Turnover Intention - G. M. Azmal Ali Quaosar; Nazifa Anbar Saba; Md Abidur Rahman (Bina Nusantara University, 2026)
In today’s competitive organizational landscape, employee commitment and retention have emerged as critical determinants of core organizational success. The research explored the antecedents of job satisfaction and its subsequent impact on organizational commitment among the employees. Grounded in social exchange theory and organizational support theory, the research highlighted transformational leadership, organizational culture, and organizational justice as primary drivers that significantly influenced and contributed to employees’ job satisfaction. Using quantitative methods, data were collected from 246 Human Resources (HR) executives through a convenience sampling method from the manufacturing and service industries of Bangladesh and analyzed using Structural Equation Modelling (SEM) in SmartPLS. The findings reveal that transformational leadership, organizational culture, and organizational justice have a significant and positive influence on employees’ job satisfaction, and, conversely, job satisfaction affects employees’ organizational commitment. Moreover, the result shows that job satisfaction exerts a significant association with turnover intentions, indicating that increased job satisfaction diminishes the chances of employees’ intention to leave the organization. The research advances the understanding of how enhancing job satisfaction can serve as a strategic tool for cultivating long-term organizational commitment, extending Western-centric theories to a developing economy country like Bangladesh. The research helps to improve continuance commitment to the organization and reduce turnover. Moreover, by integrating key antecedents and using Importance-Performance Map Analysis (IPMA), it offers both theoretical and practical contributions for HR practices to reduce turnover and enhance commitment.